조선시대 기록물의 생산 및 처리과정과 보존 - 이한희 (서지학연구, 0(37), 2007)
이 연구는 조선시대의 기록물 관리에 대한 그 사상적 배경과 문서관리 의식 및 관련된 제도 등을 알아보기 위한 연구이다.본 논문을 요약하면 다음과 같다.첫째, 조선시대의 법규정, 제도 등 기본적인 분석요소들은 조선왕조실록, 법전류, 중기류, 각종 고문서 등의 문헌들을 조사하여 즉 사료에 의한 관련 항목들을 분석하였다. 중국의 법률을 적용한 대명률직해와 경국대전 등 각종 법전에서 보이는 공문서의 다양한 작성 서식, 이첩(移牒) 유형, 보존방법 및 보존기간 등의 규정을 알 수 있었다.둘째, 전통시대의 기록물의 수집 및 처리과정은 정확하게 실제적인 모습을 알 수는 없으나 예전의 법 규정에 나와 있는 규정들과 현전(現傳)하는 고문서 등에 의하여 기록물의 수집 및 처리과정을 유추해 볼 수 있었다. 기록물의 수집 및 처리과정도 전통시대의 경우 오늘날과 유사한 처리과정을 가지고 있다. 의정부나 가각고 등과 같은 기관에서 기록물의 수집, 처리, 이관, 보관 등으로 현대의 기록물 수집, 처리과정과 비슷한 처리과정을 보여주었다.셋째, 조선시대의 기록물 보관보존의 경우 현대의 기록물보존소와 유사한 가각고가 있었으며, 사고(史庫)를 비롯한 문서고, 호적고 등과 같은 기관들을 중앙에는 물론 지방에 까지 보유하고 있어서 각종 기록물을 생산하고, 관리 보존하여 영구히 후세에 전하려던 노력을 사료와 기록에서 확인하였다. 또 실록이나 각종 문서에서 보존을 위하여 고안되거나 시행된 여러 방안들과 제도를 찾아볼 수 있었다. This study is carried out to investigate the thoughts on records management and the characteristics of the archives management system in the Joseon Period.Major findings of this study are as follows.1, Such essential elements as laws and regulations of the Joseon(朝鮮) Period were analyzed by examining The True Record of the Joseon Dynasty(朝鮮王朝實錄), various codes of laws(法典類), Joong-Gi(重記) that is traditional government records and ancient manuscripts(古文書). By investigating DaeMyungRyul- JikHae(大明律直解) and KyungKookDaeJeon(經國大典) we could learn about the various rules of the forms, communications among government offices, and the period and method of keeping official documents in the Joseon period.2. It is not known exactly how to collect and process records in the old days. The analysis of codes of laws and rules and the existing documents, however, enables us to presume the rough outline of those processes. The methods and processes of records management of such institutions as UeiJeongboo(議政府) or Gaggakgo(架閣庫) in the old days are similar to how to collect, manage, communicate, and preserve records in the present time. 3. In the Joseon Dynasty, there were Gagakgo(架閣庫), Sago(史庫), Moonseogo(文書庫), and Hojeokgo(戶籍庫) which are similar to modern archives, and whose primary functions are to create, manage, preserve and transfer records to the future generations. Since there was no central records management institution, records were managed by separate local institutions, and therefore, not properly managed.Sillok(實錄) and various other historical records document the methods and systems of preserving records. For instance, when Moonseogo(文書庫) was destroyed by fire, it was relocated to an isolated area, and people were prohibited from living in its neighborhood. KCI Citation Count: 6